1993
DOI: 10.1016/0014-5793(93)81633-b
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of NH2 and COOH‐terminal sequences destroys function of the Ca2+ ATPase of rabbit fast‐twitch skeletal muscle sarcoplasmic reticulum

Abstract: Deletion mutants of the Ca*+ ATPase of rabbit fast-twitch skeletal muscle sarcoplasmic reticulum (SERCAla) were constructed and expressed in COS-1 cells. The mutants were expressed at levels 7-to 15-fold lower than the wild-type and were inactive. In vitro transcription-translation-insertion experiments showed that deletion of transmembrane sequences M, and M,, but not of M,, M,, M,, or the NH,-terminal 30 amino acids inhibited the stable insertion of the enzyme into the membrane. Thus there was no correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Deletion of the N-terminal domain of SERCA1 reduced protein expression (13). Accordingly, mutation of SERCA2b Asn-39 to Asp or Thr reduced protein expression, suggesting that the integrity of the N terminus is important for pump expression.…”
Section: Protein Levels Of Serca2bmentioning
confidence: 99%
“…Deletion of the N-terminal domain of SERCA1 reduced protein expression (13). Accordingly, mutation of SERCA2b Asn-39 to Asp or Thr reduced protein expression, suggesting that the integrity of the N terminus is important for pump expression.…”
Section: Protein Levels Of Serca2bmentioning
confidence: 99%
“…Tryptic digestion of this ATPase provided experimental evidence for the first eight transmembrane segments that had been predicted, but an unexpected cleavage between H9 and H10 was observed (12). Mutagenesis to generate Ca 2ϩ transport mutants provided evidence that H4, H5, H6, and H8 were in the membrane domain (15)(16)(17)(18). The crystal structure of the SR Ca 2ϩ -ATPase at 14-Å resolution shows that the membrane domain can accommodate 10 membrane-spanning segments (23).…”
Section: ؉mentioning
confidence: 99%
“…These results show that the amino acid residues in the Ala 3 -Ser 6 region are not essential for Ca 2ϩ transport function. Previously, Skerjanc et al (16) reported that there is no indication from site-directed mutagenesis that specific residues in the Glu 2 -His 32 region are crucial for enzymatic activity. This is consistent with our above conclusion.…”
Section: Effects Of Deletions and Substitutions Of Residues In The Nhmentioning
confidence: 99%
“…It was previously shown (16) that deletion of most of the residues (Glu 2 -His 32 ) in the NH 2 -terminal domain results in greatly reduced expression in COS-1 cells and inactivation of the enzyme. This raises the possibility that the NH 2 -terminal domain has a region sensitive to the endoplasmic reticulum (ER)-mediated quality control, the machinery of which recognizes and rapidly degrades misfolded proteins (this misfolding can be induced by mutations) and denatured proteins to suppress their cellular expression or accumulation (17,18).…”
mentioning
confidence: 99%